The Difference in Estimated Glomerular Filtration Rate (EGFR) Between Controlled and Uncontrolled Type 2 Diabetes Mellitus Patients at Pasar Rebo General Hospital, Jakarta - Salsabila, Anissa; Putri, Dian Eka (CV. Publikasi Indonesia, 2025)
Type 2 Diabetes Mellitus (T2DM) is a metabolic disease that can lead to complications such as diabetic nephropathy, characterized by a decline in renal filtration function. Glycated hemoglobin (HbA1c) is used to classify patients into controlled (HbA1c <7%) and uncontrolled (HbA1c ≥7%) groups. Kidney function is assessed by measuring the estimated Glomerular Filtration Rate (eGFR). This study aims to determine the differences in eGFR values between controlled and uncontrolled T2DM patients. This cross-sectional study used secondary data from T2DM patients visiting the internal medicine clinic at Pasar Rebo Regional General Hospital, Jakarta, between January and December 2024. The subjects were categorized into controlled and uncontrolled groups based on HbA1c values. Inclusion criteria included patients diagnosed with diabetes in the last 5 years, aged 50-59 years, and having complete baseline data, including HbA1c and serum creatinine values. eGFR was estimated using the 2021 CKD-EPI formula. A normality test was performed on eGFR values between the two subgroups, with p>0.05 indicating a significant difference. The study of 100 T2DM subjects at Pasar Rebo Regional General Hospital found that the average eGFR value in the controlled group was 73.50, while in the uncontrolled group it was 56.92 mg/dL. An independent sample T-test showed a significant difference in eGFR values between the controlled and uncontrolled groups (p<0.001). Conclusion: There was a significant difference in eGFR values between controlled and uncontrolled T2DM patients at Pasar Rebo Regional General Hospital, Jakarta.